A comparative study of intra-peritoneal instillation of lignocaine versus placebo on operative site in laparoscopic cholecystectomy - Mundra, Mukund; Kumar, Vinod (International Surgery Journal, 2018)
Background: Visceral nociception is a significant source of the post-operative morbidity in Laparoscopic cholecystectomy and thus the idea of intraperitoneal local anaesthetic (IPLA) instillation was promulgated. The aim of the study was to evaluate the role of intra-peritoneal lignocaine instillation on post-operative morbidity in terms of post-operative pain and post-operative nausea and vomiting and also to establish if there is any difference exists between the timing of instillation of intra-peritoneal lignocaine (before and after completing the gall bladder dissection). Methods: Eighty patients randomized into two groups lignocaine group (lignocaine instilled in gallbladder bed) and placebo group (saline instilled in gallbladder bed). Lignocaine group further divided into subgroups i.e. pre-dissection lignocaine group (lignocaine instilled before gallbladder dissection) and post-dissection lignocaine group (lignocaine instilled after gallbladder dissection). Results: Post-operative pain was measured in terms of the VAS score. The score was less in lignocaine group. The difference was statistically significant (p<0.05) at 1, 2, 4, 6, 12 and 24hours between lignocaine group and placebo Group. No statistically significant difference between the mean of VAS scores of pre-dissections lignocaine and post-dissection lignocaine subgroups. In lignocaine group, 27.8%, 75%, 41% and 25% of the subject required rescue analgesia in 1st hr, next 1-8 hr, 8-16 hr and 16-24 hr respectively. In placebo group 33.3%, 97.2%, 83.3 % and 63.9% of the subject required rescue analgesia in 1st hr, next 1-8 hr, 8-16 hr and 16-24hr respectively. The difference was found to be statistically significant (p<0.05) except at 1st hour. Post operatively nausea perception, seemed to be slightly higher in placebo group as compared to lignocaine group but difference was statistically insignificant (p>0.05). Conclusions: Intraperitoneal lignocaine instillation is an effective method to alleviate post-operative pain in patients undergoing laparoscopic cholecystectomy, whether used as pre-emptive analgesia or instilled at the end of surgery. Intraperitoneal lignocaine instillation decreases post-operative analgesia requirement, especially after the 1st post-operative hour.